Sputtered Indium‐Zinc Oxide for Buffer Layer Free Semitransparent Perovskite Photovoltaic Devices in Perovskite/Silicon 4T‐Tandem Solar Cells. Issue 6 (6th December 2020) - Ying, Zhiqin; Zhu, Yudong; Feng, Xiyuan; Xiu, Jingwei; Zhang, Rui; Ma, Xuhang; Deng, Yunsheng; Pan, Hui; He, Zhubing
Abstract: Rear transparent electrode (RTE) dominates the quality of semitransparent solar cells, which determines the overall performance of tandem devices as the top cells. Here, sputtering deposited indium‐zinc oxide (IZO) is demonstrated as effective RTE for buffer layer free semitransparent perovskite solar cell (PSC). It is revealed that the vacuum‐evaporated electron‐transport layer (C60 /BCP, v ‐ETL) has better tolerance of the bombardment in the deposition process of IZO and hence superior device performance compared to the solution‐processed ETL (PCBM/BCP, s ‐ETL). Systematical characterizations evidence that the ETL surface potential shifts at the ETL/IZO interface rather than the surface morphology variation accounts for the device performance difference. By further optimizing the thickness of BCP and perovskite layers, the semitransparent PSC exhibits the best conversion efficiency of 16.23% as well as a high transmittance of 39.46% in the wavelength span from 300 to 1200 nm. By employing the optimized semitransparent PSC as the top cell in a four‐terminal perovskite/c‐silicon tandem solar cell, a combined conversion efficiency of 24.60% is achieved. This work highlights the use of sputtered IZO in the combination of IZO/C60 effectively for high‐performance semitransparent devices. Abstract : A buffer layer free semitransparent perovskite solar cell with sputtering deposited indium‐zinc oxide as the rear transparent electrode achieves a conversion efficiency of 16.23% along with high average transmittance of 39.46% from 300 to 1200 nm. That enables a high‐performance four‐terminal perovskite/c‐Si tandem solar cell with an integrated conversion efficiency of 24.60%.